The Effect of Health Education via WhatsApp on Knowledge About Exclusive Breastfeeding in Pregnant Women Trimester III at the Salok Api Darat Sub-Puskesmas - Kurniawati Agustin; Jasmawati; Lukman Nulhakim (Formosa Journal of Applied Sciences, 2023)
The aim of the research was to determine the effect of health education via WhatsApp on knowledge about exclusive breastfeeding in third trimester pregnant women. This type of research is quasi experimental. The research design uses a One Group Pre-Test – Post-Test Design without a Control Group. The population is all third trimester pregnant women at the Salok Api Darat Sub-Puskesmas in January-November 2022 totaling 33 people. Characteristics of respondents aged between 20-35 years (100%), parity of 1 child (42.4%), and employment as housewife (90.9%). Knowledge about exclusive breastfeeding before being given health education via WhatsApp to pregnant women in the third trimester of all respondents was poor (100%) and after being given health education via WhatsApp to pregnant women in the third trimester, all respondents were good (100%). There is an influence of health education via WhatsApp on knowledge about exclusive breastfeeding in third trimester pregnant women (p value: 0.000 < α: 0.05).